Fractal MapReduce decomposition of sequence alignment - Almeida, Jonas S. (2012)
This work was supported in part by the Center for Clinical and Translational Sciences of the University of Alabama at Birmingham under contract no. 5UL1 RR025777-03 from NIH National Center for Research Resources, by the National Cancer Institute grant 1U24CA143883-01, by the European Union FP7 PNEUMOPATH (HEALTH F3 2009 222983).